The maternal uniparental disomy of chromosome 6 (upd(6)mat) "phenotype": result of placental trisomy 6 mosaicism?. Issue 6 (22nd September 2017) - Eggermann, Thomas; Oehl‐Jaschkowitz, Barbara; Dicks, Severin; Thomas, Wolfgang; Kanber, Deniz; Albrecht, Beate; Begemann, Matthias; Kurth, Ingo; Beygo, Jasmin; Buiting, Karin
Abstract: Background: Maternal uniparental disomy of chromosome 6 (upd(6)mat) is a rare finding and its clinical relevance is currently unclear. Based on clinical data from two new cases and patients from the literature, the pathogenetic significance of upd(6)mat is delineated. Methods: Own cases were molecularly characterized for isodisomic uniparental regions on chromosome 6. For further cases with upd(6)mat, a literature search was conducted and genetic and clinical data were ascertained. Results: Comparison of isodisomic regions between the new upd(6)mat cases and those from four reports did not reveal any common isodisomic region. Among the patients with available cytogenetic data, five had a normal karyotype in lymphocytes, whereas a trisomy 6 (mosaicism) was detected prenatally in four cases. A common clinical picture was not obvious in upd(6)mat, but intrauterine growth restriction (IUGR) and preterm delivery were frequent. Conclusion: A common upd(6)mat phenotype is not obvious, but placental dysfunction due to trisomy 6 mosaicism probably contributes to IUGR and preterm delivery. In fact, other clinical features observed in upd(6)mat patients might be caused by homozygosity of recessive mutations or by an undetected trisomy 6 cell line. Upd(6)mat itself is not associated with clinical features, and can rather be regarded as a biomarker. In case upd(6)mat is detected, the cause for the phenotype is identified indirectly, but the UPD is not the basic cause. Abstract : Maternal uniparental disomy of chromosome 6 (upd(6)mat) is a rare finding, and its clinical relevance is currently unclear. We report on two new cases and delineate the pathogenetic significance of upd(6)mat from these cases and those from the literature.